PENGARUH PENGGUNAAN ALAT PERAGA NUMBER MACHINE TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA MADRASAH IBTIDAIYAH - Firdaus, Fery Muhamad; Prastya, Budi (JMIE (Journal of Madrasah Ibtidaiyah Education), 2018)
This study aims to determine the effect of the use of number machine props to the mathematical reasoning ability of students of grade IV MIN 2 of South Tangerang City on the matter of integers. The number machine tool is a semi-concrete tool or a function engine that performs mathematics on the task of operation. This research was conducted in class IV MIN 2 Tangerang Selatan City. The method used in this research is quasi experimental method with the design of Nonequivalent Pretest-Posttest Control Group Design. The sample in this study consisted of 30 experimental students and control class which consisted of 29 students. The results showed that students taught by using number machine tools obtained the average value of students 'mathematical reasoning ability is higher than the average value of students' mathematical reasoning skills taught without using the number machine tool that is the significance value t_hitung <0.05. Based on result of calculation of influence test (effect size) obtained d value equal to 0,59. The value of the effect size obtained interprets that the use of number machine tool has an influence in the medium category. Thus, this indicates that there is a moderate effect of using number machine props to the students' mathematical reasoning abilities in Class IV MIN 2 Tangerang Selatan City